SCHOOL TYPE AS A PREDICTOR OF STUDENTS’ STATISTICAL LITERACY: CONTROLLING FOR GENDER AND PARENTAL EDUCATION - Elizar Elizar; Benidiktus Tanujaya; Jeinne Mumu; Cut Khairunnisak; Dwi Fadhiliani; Dewi Annisa (ALGORITMA: Journal of Mathematics Education, 2026)
Abstract In today’s data-driven era, the rapid growth of big data has made encounters with data unavoidable for everyone, including students. Therefore, preparing students with adequate statistical literacy has become increasingly important. This study employed a quantitative non-experimental design using an ex post facto approach. It examined and compared students' statistical literacy across three types of schools in Aceh, Indonesia. More specifically, the study investigated whether school type predicted students' statistical literacy after controlling for gender and parental education. Data were collected through a statistical literacy test and a brief demographic questionnaire covering gender and parental educational background. The data were analyzed using hierarchical multiple regression and Tukey HSD post hoc analysis. The findings showed that gender and parental education did not significantly influence students' statistical literacy, whereas school type did. These results suggest that different school environments may offer distinct learning experiences and opportunities for statistical reasoning and data literacy. Abstrak Di era berbasis data saat ini, pertumbuhan big data yang semakin pesat membuat setiap individu, termasuk siswa, tidak dapat terlepas dari paparan data dalam kehidupan sehari-hari. Oleh karena itu, mempersiapkan siswa dengan kemampuan literasi statistik yang memadai menjadi semakin penting. Penelitian ini menerapkan desain penelitian kuantitatif non-eksperimental dengan pendekatan ex post facto. Penelitian ini bertujuan untuk mengkaji dan membandingkan literasi statistik siswa pada tiga jenis sekolah di Aceh. Secara khusus, penelitian ini meneliti apakah jenis sekolah memprediksi literasi statistik siswa setelah mengontrol gender dan pendidikan orang tua. Data dikumpulkan melalui tes literasi statistik dan kuesioner singkat terkait gender serta latar belakang pendidikan orang tua. Data dianalisis menggunakan hierarchical multiple regression dan uji lanjut Tukey HSD. Hasil penelitian menunjukkan bahwa gender dan pendidikan orang tua tidak berpengaruh signifikan terhadap literasi statistik siswa, sedangkan jenis sekolah menunjukkan pengaruh yang signifikan. Temuan ini mengindikasikan bahwa lingkungan sekolah yang berbeda dapat memberikan pengalaman belajar dan kesempatan yang berbeda pula dalam mengembangkan kemampuan penalaran statistik dan literasi data siswa.